Crown Lengthening Surgery in the Esthetic Area for Optimized Results: A Review with Surgical Recommendations - Sérgio Kahn; Walmir Júnio de Pinho Reis Rodrigues; Alexandra Tavares Dias; Rodrigo Resende; Juliana Campos Hasse Fernandes; Gustavo Vicentis Oliveira Fernandes (Surgeries)
Background: Crown lengthening (CL) in esthetic areas has become a versatile procedure with applications in many clinical situations. Knowledge concerning different periodontal phenotypes, and the supracrestal tissue attachment (STA)—former biological width—has allowed for a better understanding of surgical management, allowing for the individualization of surgical therapy. This review presented an individualized surgical approach to CL in esthetic areas based on evaluating the phenotype and current considerations about the STA, correlating them to suggestive surgical techniques. Methods: For an individualized surgical approach, it is primarily necessary to understand STA, including the relationship and distance between the cementoenamel junction (CEJ) and the bone crest (BC) and the position of the free gingival margin (FGM); secondarily, it is necessary to verify the periodontal phenotype to prepare surgical planning (gingivectomy or osseous resection/contouring). Three periodontal phenotypes are recognized, presenting different biological behaviors due to specific characteristics implicitly correlated to soft tissue management. Results: Then, after assessing the distance from the CEJ to the BC, the position of the FGM, and the periodontal phenotype, it is possible to individualize the treatment according to the phenotype. In cases of a thin and scalloped periodontium with delicate gingiva, there might be the presence of bone dehiscence, fenestration, and instability in the healing of the gingival margin, bringing extra attention to tissue manipulation and suggesting a minimally invasive technique (no flap). A partial-thickness flap is recommended for a thick and scalloped periodontium, keeping the periosteum adhered to the bone. For periodontium B (fibrous and dense gingiva and tissue resistant to injuries), the surgical approach recommended is an open full-thickness flap with osteotomy for horizontal and vertical bone volume removal. Then, observing first the specific parameters, such as the STA, CEJ, BC, FGM, and KTW, and then the characteristics of periodontal phenotypes, it is possible to determine the individualized surgical strategy and a reasonable surgical approach to tissue manipulation in clinical CL surgeries. Conclusions: The surgical approach must be defined according to individualized planning since several variables can influence the dynamics of the periodontal tissues.